Genetic and Phenotypic Characterization of the Etiological Agent of Canine Orchiepididymitis Smooth Brucella sp. BCCN84.3 - Guzmán-Verri, Caterina; Suárez-Esquivel, Marcela; Ruíz-Villalobos, Nazareth; Zygmunt, Michel S.; Gonnet, Mathieu; Campos, Elena; Víquez-Ruiz, Eunice; Chacón-Díaz, Carlos; Aragón-Aranda, Beatriz; Conde-Álvarez, Raquel; Moriyón, Ignacio; Blasco, José María; et al. (Frontiers in Veterinary Science, 2019)
Members of the genus Brucella cluster in two phylogenetic groups: classical and non-classical species. The former group is composed of Brucella species that cause disease in mammals, including humans. A Brucella species, labeled as Brucella sp. BCCN84.3, was isolated from the testes of a Saint Bernard dog suffering orchiepididymitis, in Costa Rica. Following standard microbiological methods, the bacterium was first defined as “Brucella melitensis biovar 2”. Further molecular typing, identified the strain as an atypical “Brucella suis”. Distinctive Brucella sp. BCCN84.3 markers, absent in other Brucella species and strains, were revealed by fatty acid methyl ester analysis, high resolution melting PCR and omp25 and omp2a/omp2b gene diversity. Analysis of multiple loci variable number of tandem repeats and whole genome sequencing demonstrated that this isolate was different from the currently described Brucella species. The smooth Brucella sp. BCCN84.3 clusters together with the classical Brucella clade and displays all the genes required for virulence. Brucella sp. BCCN84.3 is a is a species nova taxonomical entity displaying pathogenicity; therefore, relevant for differential diagnoses in the context of brucellosis. Considering the debate on the Brucella species concept, there is a need to describe the extant taxonomical entities of these pathogens in order to understand the dispersion and evolution.